Analyze the use of probiotic straps in the treatment of acute diarrhea (Research, Society and Development, 2020)
Probiotic strains are generally live microorganisms that have little or no pathogenicity, added to foods, medicines and dietary supplements. The purpose of this review is to analyze the use of probiotic strains in the treatment of acute diarrhea. The data were obtained through a search in the Pubmed, Scielo and Lilacs databases in English, Portuguese and Spanish. All articles were selected from reading the title and summary that analyzed probiotic strains in the treatment of acute diarrhea. To retrieve the desired information, the descriptors and Boolean logic were applied using the following terms of interest: (“Probiotic”) AND (Saccharomyces boulardii) OR (Lactobacillus rhamnosus) OR (Lactobacillus reuterii) AND ("acute diarrhea") NOT ( review). Initially, 184 studies were found on the use of probiotics in the treatment of acute diarrhea, of which 163 were found in the Pubmed database, 11 in Scilelo and 10 in Lilacs. After the exclusion and inclusion selection criteria, 7 studies were published in Pubmed, 1 study in Scielo and no study in Lilacs, totaling 8 studies included in the review. The results showed that probiotics, when administered in adequate doses, can reduce the duration and frequency of bowel movements to patients with acute diarrhea.